Artistic, Visual Thought Processes Supporting High Achievement - Ambrose, Don (International Journal for Talent Development and Creativity, 2023)
This interdisciplinary, conceptual analysis addresses the nature and benefits of artistic processes in learning andwork. While recognizing various forms of artistry, the emphasis is on visual-spatial thinking. The benefits of thiskind of thinking in academic and professional activities include the simplification of massively complex writing,improvement of psychological functioning, and the magnification of creative work in various professions,especially in science, technology, engineering, and mathematics (STEM) fields. Visual-spatial thinking also is astrength that often helps twice-exceptional individuals overcome their learning difficulties. Several thinking andlearning strategies are explored, including visual data animation, concept cartooning, visual metaphor, andmusical translation of written material. Some ways that visual-spatial thinking can help overcome the problemsgenerated by dogmatic school reform also are scrutinized.